Investigating mechanical characteristics of styli for micro-CMMs - Ismail, Mohd; Tseng, Kuo-Yu; Claverley, James David; Sheu, Dong-Yea; Chetwynd, Derek; Leach, Richard K. (2016)
The mechanical characteristics of styli for micro coordinate measuring machines (micro-CMMs) is of importance because of the major effect the styli have on the performance and capability of micro-CMMs. Previous work has focussed on the design of the next generation of stylus systems for micro-CMMs, and several test styli have been manufactured. These test styli have sphere-tips and stylus shaft diameters of less than 70 gm and 40 pm respectively, and aspect ratios of greater than ten. The styli are manufactured using a novel hybrid manufacturing process. In this paper the results of tests designed to determine the mechanical properties of the test styli will be presented. The experimental setup and testing method has been enhanced from that of the previous work, especially with respect to the precision manipulation stages and control software. The main focus of the work presented here is to measure the stiffness of the styli shafts and the transverse force on the tip that causes initial plastic behaviour in the stylus. The results of the mechanical properties measurements are also compared to results from analytical models. The outcome of this work will lead to a better understanding of the development of tactile stylus systems for micro-CMMs, with the aim of developing micro-styli with sphere-tip diameters of the order of 10 pm or less.